Byzantine and Post-Byzantine Religious Objects from Cilicia (Southern Turkey) - Laflı, Ergün; Buora , Maurizio; Çetingöz , Alev (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2025)
In this paper we present 95 Byzantine and Post-Byzantine liturgical and devotional objects stored in eight local museums in Cilicia in southern Turkey. This corpus provides detailed analysis of several groups of metalwork. The study aims to illuminate the religious life of Christian communities in Byzantine and Post-Byzantine Cilicia.